2021
DOI: 10.3389/fcimb.2021.593077
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of gRNAs Targeting Genetic Variants Across HIV-1 Subtypes for CRISPR-Mediated Antiviral Therapy

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR)-based HIV-1 genome editing has shown promising outcomes in in vitro and in vivo viral infection models. However, existing HIV-1 sequence variants have been shown to reduce CRISPR-mediated efficiency and induce viral escape. Two metrics, global patient coverage and global subtype coverage, were used to identify guide RNA (gRNA) sequences that account for this viral diversity from the perspectives of cross-patient and cross-subtype gRNA design, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…The strategies that target viral sequences, such as HIV DNA excision, may encounter problems with HIV diversity and the selection of effective sgRNAs ( Yoder, 2019 ). In such cases, a personalized approach in sgRNA design would help make therapy more effective ( Dampier et al., 2018 ; Chung et al., 2021 ).…”
Section: Perspectives In Crispr/cas Anti-hiv Therapy and Concluding R...mentioning
confidence: 99%
“…The strategies that target viral sequences, such as HIV DNA excision, may encounter problems with HIV diversity and the selection of effective sgRNAs ( Yoder, 2019 ). In such cases, a personalized approach in sgRNA design would help make therapy more effective ( Dampier et al., 2018 ; Chung et al., 2021 ).…”
Section: Perspectives In Crispr/cas Anti-hiv Therapy and Concluding R...mentioning
confidence: 99%
“…They compared single and dual gRNAs targeting different HIV-1 regions and found that the latter approach showed no virus replication and no escape for up to 60 days, extended to an even longer period for gRNA combinations targeting highly conserved sites (112). To aid the design of more broad-acting and effective gRNA sequences, in silico predictive pipelines based on sequences shared by genetic variants and viral subtypes have been developed (113,114). This further optimization may help in reducing viral escape from the CRISPR-Cas9 system.…”
Section: Crispr-cas9 Gene Editingmentioning
confidence: 99%
“…Furthermore, the problem of the emergence of resistant viruses may be overcome by targeting highly conserved sequences, as it is less probable that a functional resistant mutant could be generated. It is well known that HIV-1 displays a great inter-and intra-patient variability, so bioinformatic pipelines have come in handy to predict what are the most conserved sequences among different variants and, thus, select the possible most efficient broad-spectrum gRNAs in order to be effective in as many patients as possible [42,43].…”
Section: Considerations On the Design Of The Grnasmentioning
confidence: 99%